Effects of intestinal microbiota on physiological metabolism and pathogenicity of Vibrio - Sun, Han; Zhu, Changliang; Fu, Xiaodan; Khattak, Shakir; Wang, Jingyu; Liu, Zhihao; Kong, Qing; Mou, Haijin; Secundo, Francesco (Frontiers in Microbiology, 2022)
Vibrio species are disseminated broadly in the marine environment. Some of them can cause severe gastroenteritis by contaminating seafood and drinking water, such as Vibrio parahaemolyticus, V. cholerae and V. vulnificus. However, their pathogenic mechanism still needs to be revealed to prevent and reduce morbidity. This review comprehensively introduces and discusses the infection process of Vibrio including adhesion, invasion, cell colonization and proliferation, and resistance to host immunity. Vibrio usually produces pathogenic factors including hemolysin, type III secretion system, and adhesion proteins. Quorum sensing, a cell molecular communication system between the bacterial cells, playing an important role in Vibrio intestinal invasion and colonization. Human immune system can limit virulence of Vibrio or even kill the bacteria through different responses. Intestinal microflora is a key component of the immune system, but information on its effects on physiological metabolism and pathogenicity of Vibrio is seldom available. In this review, effects of intestinal microorganisms and their metabolites on the invasion and colonization of common pathogenic Vibrio and VBNC status cells are discussed, which is conducive to finding the next-generation prebiotics. Strategy of dietary intervention is discussed for food safety control. Finally, future perspectives are proposed to prevent Vibrio infection in the aquaculture.